Neuromonitoring in Neonatal-Onset Epileptic Encephalopathies - Trollmann, Regina (Frontiers in Neurology, 2021)
Considering the wide spectrum of specific etiologies of neonatal seizures and their unfavorable consequences on long-term neurodevelopmental prognosis, long-term and bedside neuromonitoring in at-risk neonates is increasingly important. Early identification of prolonged seizure activity and acute complications as well as therapy monitoring represent crucial and multidisciplinary tasks. According to the American Clinical Neurophysiology Society (2011) and ILAE Neonatal Task Force guidelines (2018), EEG is essential and highly sensitive for diagnosing and monitoring neonatal seizures. Amplitude-integrated EEG (aEEG), a useful bedside monitoring method, is highly recommended, but as a complementary tool because of methodical limitations. Variability in maturational pattern and electroclinical dissociation make interpreting diagnostic and prognostic EEG parameters in very preterm neonates particularly challenging. The special role of aEEG in monitoring neonates with so-called electrographic-only or subtle seizures, as well as patients with hypoxic-ischemic, metabolic, or genetic encephalopathies who are at high risk of prolonged seizures and status epilepticus, is well documented. Of interest, established prognostic EEG parameters (e.g., in perinatal hypoxic-ischemic encephalopathy) need to be revised, in part. Progress in the etiological identification of rare neonatal-onset genetic epileptic encephalopathies and in the classification of electroclinical patterns and long-term monitoring data may open novel precision medicine-based therapeutic options.